Improvement of copper stress tolerance in pepper plants (Capsicum annuum L.) by inoculation with arbuscular mycorrhizal fungi - Ruscitti, Marcela Fabiana (2017)
The effect of arbuscular mycorrhizal fungi (AMF) inoculation, on pepper plant growth and physiological parameters in response to increasing soil Cu concentrations was studied. Treatments consisted of inoculation or not with Funneliformis mosseae or Rhizophagus intraradices and the addition of Cu to soil at concentrations of 0, 2, 4 and 8 mM CuSO₄. The increase in copper concentration diminished the inoculation in all treatments. The highest experimental concentration of Cu (8 mM) reduced significantly the hyphae viability and ALP activity, regardless of the inocula used. The total dry weight and the leaf area were higher for mycorrhizal plants. The mycorrhizal dependence was 30 and 50% for plants inoculated with F. mosseae and R. intraradices, respectively at 8 mM CuSO4. The electrolyte leakage was higher at higher Cu concentrations, in roots and leaves. Net photosynthetic rates and transpiration were lower in plants treated with Cu, regardless of the inocula. At low Cu concentration in soil no differences were observed in Cu content in the shoots and roots. At 4 mM Cu, Cu content in roots was significantly higher than in shoots. At 8 mM Cu, in non-inoculated plants accumulate more Cu than inoculated plants in the roots, leaves and fruits regardless of the inocula. Beneficial microbial inoculants such as AMF, is an attractive strategy to farmers in the context of sustainable agriculture. Pre-inoculation in transplants could be an adequate practice to alleviate the deleterious effects in stress of pepper plants. However different AMF species can differ in their ability to minimize stress effects and promote plant growth.